Factors influence the awareness of general takaful product among client of Iltizam Perkasa Sdn Bhd / Siti Syuhadah Mohamad Isa @ Azmi - Mohamad Isa @ Azmi, Siti Syuhadah (2011)
According to the topic chosen on factors influence the awareness of general takaful product among of client Iltizam Perkasa Sdn Bhd, it is the one of key the level of awareness. Research objectives for this study undertaken are to identify types of general takaful product available in Malaysia, to determine the level of awareness of Iltizam’s client towards general takaful product and to determine the factors influence level of awareness towards general takaful product in this research. The scope of study is mainly focus on the clients of Iltizam awareness towards general takaful product. A set of questionnaire was distributed to the respective respondent. The data is analyzed using descriptive analys